Amniotic Membrane as a Main Component in Treatments Supporting Healing and Patch Grafts in Corneal Melting and Perforations. (14th February 2020) - Krysik, Katarzyna; Dobrowolski, Dariusz; Wylegala, Edward; Lyssek-Boron, Anita
Abstract : Purpose . To report on surgical approaches using amniotic membrane applications and patch grafts in corneal melting and perforations. Anatomical and functional results, including advantages and disadvantages of the interventions, will also be explored. Methods . A five-year retrospective analysis of 189 surgical treatments involving corneal melting with perforation was performed. In one evaluated treatment type, a graft of amniotic membrane, often folded one to three times, was sutured with the epithelial side facing the previously mechanically debrided corneal tissue. A larger monolayer amniotic patch was then sutured, with the epithelial side facing the top of the first membrane, to the perilimbal conjunctiva. For corneal patch grafts, the size-fitting technique of graft trephination was applied, and the donor-recipient junctions were sewn with interrupted sutures. All the procedures were evaluated, noting outcomes and complications of surgery, preoperative and postoperative visual acuities, postoperative intraocular pressures, graft rejection, and other late comorbidities and complications. Results . We performed 119 amniotic membrane applications (63%) and 70 corneal patch grafts (37%). Anatomical reconstruction of the anterior chamber was achieved in 157 eyes, of which 102 eyes (86%) received an amniotic membrane and 55 eyes (79%) were treated with the patch graft technique. In 63 eyes (33%), more than one amnion or graft treatment was necessary to close the corneal perforation. Conclusions . The success of medical and surgical management depends on the cause of corneal melting, and amniotic membrane applications often require further intervention; nevertheless, patch grafts deliver better tectonic reconstruction than amniotic membrane alone.